Adult Javanese migrants to Indonesian Papua at high risk of severe disease caused by malaria. - Baird, J; Basri, H; Weina, P; MaGuire, J; Barcus, M; Picarema, H; Elyazar, I; Ayomi, E; Sekartuti (2003)
Migrants from Java arrive in hyperendemic Papua, Indonesia lacking exposure to endemic malaria. We evaluated records of evacuation to hospital with a diagnosis of severe malaria from a transmigration village in northeastern Papua. During the first 30 months, 198 residents with severe disease were evacuated (7.5 evacuations/100 person-years). During this period the risk of evacuation for adults (> 15 years of age) was 2.8. (95% CI = 2.1-3.8; P < 0.0001) relative to children, despite apparently equal exposure to risk of infection. Relative risk (RR) for adults was greatest during the first 6 months (RR > 16; 95% CI > or = 2.0-129; P = 0.0009), and diminished during the second 6 months (RR = 9.4; 95% CI = 2.7-32.8; P < 0.0001) and the third 6 months (RR = 3.7; 95% CI = 1.7-7.9; P = 0.0004). During the next two 6-month intervals, the RR for adults was 1.6 and 1.5 (95 % CI range 0.8-2.6; P < 0.18). Adults lacking chronic exposure were far more likely to progress to severe disease compared to children during initial exposure, but not after chronic exposure to infection.